Question
Which expression is equivalent to
. Assuming ![m \neq 0; n\neq 0](https://tex.z-dn.net/?f=m%20%5Cneq%200%3B%20n%5Cneq%200)
Answer:
![\frac{4m^3}{n^5}](https://tex.z-dn.net/?f=%5Cfrac%7B4m%5E3%7D%7Bn%5E5%7D)
Step-by-step explanation:
Given
![\frac{4mn}{m^{-2}n^6}](https://tex.z-dn.net/?f=%5Cfrac%7B4mn%7D%7Bm%5E%7B-2%7Dn%5E6%7D)
Required:
Simplify
To simplify this, we start by splitting each individual function
![\frac{4mn}{m^{-2}n^6} = \frac{4m}{m^{-2}} * \frac{n}{n^6}](https://tex.z-dn.net/?f=%5Cfrac%7B4mn%7D%7Bm%5E%7B-2%7Dn%5E6%7D%20%3D%20%5Cfrac%7B4m%7D%7Bm%5E%7B-2%7D%7D%20%2A%20%5Cfrac%7Bn%7D%7Bn%5E6%7D)
From laws of indices
![\frac{a^x}{a^y} = a^{x-y}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%5Ex%7D%7Ba%5Ey%7D%20%3D%20a%5E%7Bx-y%7D)
SO, the above expression can also be expressed the same way
![\frac{4m}{m^{-2}} * \frac{n}{n^6} = 4m^{1-(-2)} * n^{1-6}](https://tex.z-dn.net/?f=%5Cfrac%7B4m%7D%7Bm%5E%7B-2%7D%7D%20%2A%20%5Cfrac%7Bn%7D%7Bn%5E6%7D%20%3D%204m%5E%7B1-%28-2%29%7D%20%2A%20n%5E%7B1-6%7D)
![\frac{4m}{m^{-2}} * \frac{n}{n^6} = 4m^{1+2)} * n^{1-6}](https://tex.z-dn.net/?f=%5Cfrac%7B4m%7D%7Bm%5E%7B-2%7D%7D%20%2A%20%5Cfrac%7Bn%7D%7Bn%5E6%7D%20%3D%204m%5E%7B1%2B2%29%7D%20%2A%20n%5E%7B1-6%7D)
![\frac{4m}{m^{-2}} * \frac{n}{n^6} = 4m^{3} * n^{-5}](https://tex.z-dn.net/?f=%5Cfrac%7B4m%7D%7Bm%5E%7B-2%7D%7D%20%2A%20%5Cfrac%7Bn%7D%7Bn%5E6%7D%20%3D%204m%5E%7B3%7D%20%2A%20n%5E%7B-5%7D)
From laws of indices,
![a^{-x} = \frac{1}{a^x}](https://tex.z-dn.net/?f=a%5E%7B-x%7D%20%3D%20%5Cfrac%7B1%7D%7Ba%5Ex%7D)
So,
![\frac{4m}{m^{-2}} * \frac{n}{n^6} = 4m^{3} * \frac{1}{n^5}](https://tex.z-dn.net/?f=%5Cfrac%7B4m%7D%7Bm%5E%7B-2%7D%7D%20%2A%20%5Cfrac%7Bn%7D%7Bn%5E6%7D%20%3D%204m%5E%7B3%7D%20%2A%20%5Cfrac%7B1%7D%7Bn%5E5%7D)
![\frac{4m}{m^{-2}} * \frac{n}{n^6} = \frac{4m^3}{n^5}](https://tex.z-dn.net/?f=%5Cfrac%7B4m%7D%7Bm%5E%7B-2%7D%7D%20%2A%20%5Cfrac%7Bn%7D%7Bn%5E6%7D%20%3D%20%5Cfrac%7B4m%5E3%7D%7Bn%5E5%7D)
Hence,
is equivalent to ![\frac{4m^3}{n^5}](https://tex.z-dn.net/?f=%5Cfrac%7B4m%5E3%7D%7Bn%5E5%7D)
Answer:
x=3
Step-by-step explanation:
Since they are similar triangles, we can use ratios to solve
x 3.5
----- = -------
6 7
Using cross products
7x = 21
Divide each side by 7
7x/7 = 21/7
x = 3
Draw a line straight down the middle to get 2 equilaterals.